A crisis communication plan for municipalities: the case of the Frances Baard district municipality - Kunguma, Olivia; Terblanche, Lydie (Department of Communication Science, University of the Free State, 2013)
A crisis communication plan facilitates the effective flow of information between relevant organisation(s) and a community affected by a crisis. In 2010 the Frances Baard District Municipality, situated in the Northern Cape, commissioned the development of a crisis communication plan for the municipality. It was to be developed in consultation with various stakeholders. Once developed, the plan had to be reviewed and serve as an educational document that could be used by other municipalities. The study found that drafting a crisis communication plan has to include best communication practices for each anticipated problem and effective implementation. Continuous evaluation and updating of the plan are necessary to ensure that critical business functions are not jeopardised in the event of a crisis.
Keywords: Municipality; South Africa; Northern Cape; Crisis